Efficient revocable certificateless remote anonymous authentication protocol for wireless body area network - Shun ZHANG; Hongli FAN; Hong ZHONG; Miaomiao TIAN (Tongxin xuebao)
To ensure the security and privacy of patients’ health data in wireless body area network (WBAN),communication parties must be mutual authenticated.Now some bilinear pairings led to a larger computation cost for users and tree structure revocation would lead to larger user storage cost.In order to achieve revocation and reduce the cost of the user side,a novel revocable certificate less remote anonymous authentication protocol for WBAN was proposed by using elliptic curve cryptography and revoke algorithm that could revoke users by updating their time-private-keys.Security requirements including anonymity,mutual authentication and session key establishment were satisfied in proposed scheme.Compared with the existing schemes,the experimental analysis shows that the computation cost and storage cost of the authentication protocol are greatly reduced,which is more suitable for resource-constrained WBAN.Security analysis also shows that the protocol is secure in the random oracle model.